2017
DOI: 10.3389/fpsyg.2017.00881
|View full text |Cite
|
Sign up to set email alerts
|

Judgments at Gaze Value: Gaze Cuing in Banner Advertisements, Its Effect on Attention Allocation and Product Judgments

Abstract: Banner advertising is a popular means of promoting products and brands online. Although banner advertisements are often designed to be particularly attention grabbing, they frequently go unnoticed. Applying an eye-tracking procedure, the present research aimed to (a) determine whether presenting human faces (static or animated) in banner advertisements is an adequate tool for capturing consumers’ attention and thus overcoming the frequently observed phenomenon of banner blindness, (b) to examine whether the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…Although the results of Janiszewski et al (2013) are promising and in line with observations from marketing research that increased visual attention on a product increases the product’s preference (Chandon et al, 2009; Palcu et al, 2017), they are nevertheless limited. The reason is that, for constructing stimulus pairs for the preference-choice task whose items were originally of equal preference, the researchers used products that were unknown to the participants.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although the results of Janiszewski et al (2013) are promising and in line with observations from marketing research that increased visual attention on a product increases the product’s preference (Chandon et al, 2009; Palcu et al, 2017), they are nevertheless limited. The reason is that, for constructing stimulus pairs for the preference-choice task whose items were originally of equal preference, the researchers used products that were unknown to the participants.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, consumers are exposed to visually complex environments in many supermarkets and online shops, where they selectively attend to some products and neglect others. Furthermore, marketing applies tools to create selective attention, for example, by shelf placements (Atalay et al, 2012) or gaze cueing (Palcu et al, 2017). Finally, selective attention could be easily implemented as advertising in computer games.…”
Section: Introductionmentioning
confidence: 99%
“…Eye tracking research has also revealed how the composition of marketing information guides attention and subsequently impacts evaluation and choice. For instance, in a study by Palcu et al (2017) participants were presented with online advertisement banners showing faces and products. The authors manipulated whether the models’ gaze was directed at the product.…”
Section: Physiological and Neuroscientific Measures Used In Consumer mentioning
confidence: 99%
“…Previous studies show that the gaze direction of a model may influence the evaluation of advertised products and advertisements (Adil, Lacoste-Badie, & Droulers, 2018;Palcu, Sudkamp, & Florack, 2017). Therefore, the difference in gaze direction between the two conditions may potentially have confounded the effect of face orientation on the evaluation of the displayed product.…”
Section: Discussionmentioning
confidence: 99%
“…This composition might have resulted in the model in the leftward condition appearing to avert her gaze from the product, while the model in the rightward condition seems to be gazing directly toward the product. Previous studies show that the gaze direction of a model may influence the evaluation of advertised products and advertisements (Adil, Lacoste‐Badie, & Droulers, 2018; Palcu, Sudkamp, & Florack, 2017). Therefore, the difference in gaze direction between the two conditions may potentially have confounded the effect of face orientation on the evaluation of the displayed product.…”
Section: Discussionmentioning
confidence: 99%